Peningkatan Personal Branding Direktur CV. Utama Maju Bersama melalui Pembuatan Kartu Nama Digital - Anam, Rizqy Khairul; Maufur, Miqdam; Rohmat, Ali; Fitriyani, Yeny; Pudail, M.; Hidayat, Trian; Rahmaan, Dimas Anjanii; Risydiyani, Wilda; Jannah, Vina Roudhotul; Febriyanti, Aprillyana; Ula, Himmatul; Aini, Siti Nur (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology requires entrepreneurs to build a professional self-image that supports business sustainability. One effective strategy is digital-based personal branding. This article aims to enhance the personal branding of the director of CV. Utama Maju Bersama through the development of a digital business card using the Asset-Based Community Development (ABCD) approach. The community engagement was conducted participatorily through several stages: asset mapping, digital card design, training implementation, and evaluation of media effectiveness. The results indicate that the partner’s director was able to utilize the digital business card to strengthen personal identity in business interactions, particularly through social media, email, and communication applications. The digital business card is considered a simple, practical, and low-cost yet high-impact promotional tool that significantly improves professional impressions and business competitiveness. The ABCD approach proved relevant as it leverages existing partner assets and develops them into a sustainable personal branding strategy. This program not only enhances digital literacy but also increases business partners’ trust in the professionalism of entrepreneurs.